Pengukuran Kematangan Budaya Keselamatan Kerja dengan Metode Hudson Safety Culture Model dalam Upaya Menuju Zero Accident di PT XYZ Karawang Jawa Barat - Suhartono Suhartono; Nurulia Hidayah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Workplace safety culture is one of the key factors in preventing occupational accidents in industrial environments. Organizations with a higher level of safety culture maturity tend to demonstrate better safety performance. This study aims to measure the level of safety culture maturity at PT XYZ using the Hudson Safety Culture Model and to analyze the relationships among safety culture dimensions through Pearson correlation analysis.This research employed a quantitative method using a questionnaire instrument based on a 5-point Likert scale covering six dimensions of safety culture: Safety Leadership & Management Commitment, Safety Management System & Enforcement, Worker Participation & Safety Communication, Competency & Operational Safety Practice, Learning & Continuous Improvement, and Reporting & Just Culture. The survey was conducted at the end of 2025.The results show that the average safety culture maturity score reached 4.15, indicating that the organization has achieved the level of a Proactive Safety Culture. Pearson correlation analysis revealed strong positive relationships among the safety culture dimensions, with correlation coefficients ranging from 0.76 to 0.86. These findings indicate that improvements in one dimension of safety culture tend to reinforce other dimensions.This study concludes that strengthening safety culture through safety leadership, effective occupational safety management systems, and an open reporting culture is a critical factor in achieving the goal of zero accidents.